2003
DOI: 10.1128/jb.185.7.2143-2152.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Single Gene on the Staphylococcal Multiresistance Plasmid pSK1 Encodes a Novel Partitioning System

Abstract: The orf245 gene is located immediately upstream of, and divergently transcribed from, the replication initiation gene, rep, of the Staphylococcus aureus multiresistance plasmid pSK1, and related genes have been found in association with a range of evolutionarily distinct replication genes on plasmids from various gram-positive genera. orf245 has been shown previously to extend the segregational stability of a pSK1 minireplicon. Here we describe an investigation into the basis of orf245-mediated stabilization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…Indeed, Foley et al (1996) have demonstrated the incompatibility of two plasmids with the same ori site by providing three and a half copies of the 22 bp sequence of the pCI305 ori site in trans on a compatible vector, which leads to the loss of pCI305 from the cell population. In addition, partitionmediated incompatibility occurs when two plasmids introduced into the same cell carry identical centromerelike sites, which are indistinguishable from each other during the partitioning process, as previously reported in the Staphylococcus pSK1 plasmid (Simpson et al, 2003). The incompatibility of pGdh442 with pSK08-type plasmids will probably prevent the transfer of pGdh442 in most strains capable of growing in milk, since out of 15 tested prtPcontaining strains, 12 contained the same replication and partition genes as pSK08, as revealed by PCR amplification with specific primers (Table 1) derived from the ori, repA, parA and parB sequences of pSK08 (data not shown).…”
Section: Is Elements and Transposasesmentioning
confidence: 59%
“…Indeed, Foley et al (1996) have demonstrated the incompatibility of two plasmids with the same ori site by providing three and a half copies of the 22 bp sequence of the pCI305 ori site in trans on a compatible vector, which leads to the loss of pCI305 from the cell population. In addition, partitionmediated incompatibility occurs when two plasmids introduced into the same cell carry identical centromerelike sites, which are indistinguishable from each other during the partitioning process, as previously reported in the Staphylococcus pSK1 plasmid (Simpson et al, 2003). The incompatibility of pGdh442 with pSK08-type plasmids will probably prevent the transfer of pGdh442 in most strains capable of growing in milk, since out of 15 tested prtPcontaining strains, 12 contained the same replication and partition genes as pSK08, as revealed by PCR amplification with specific primers (Table 1) derived from the ori, repA, parA and parB sequences of pSK08 (data not shown).…”
Section: Is Elements and Transposasesmentioning
confidence: 59%
“…Furthermore, the Par protein, responsible for the stabilization of plasmid pSK1 in Staphylococcus spp. (24), could be a TubY remote homolog because it shares both the HTH and coiled-coil motifs and 45% identity at the C-terminal tail with TubY, but this plasmid lacks TubZ-R homologs. but does not carry any essential genes for C. botulinum survival.…”
Section: Resultsmentioning
confidence: 99%
“…The stability of the vancomycin-resistant plasmid in the transconjugant, S345RF, was studied in triplicate, as described, with some modifications (73). One hundred microliters of an overnight culture of the strain grown in BHI broth containing 10 g/ml vancomycin was used to inoculate 10 ml of fresh BHI broth containing 10 g/ml vancomycin and grown for 4 h. Dilutions of the culture were prepared in sterile H 2 O and plated onto nonselective BHI agar plates for viable counts.…”
Section: Isolation Of Plasmids Encoding Vancomycinmentioning
confidence: 99%